Islam and sport: from human experiences to revelation - Abd Rahim, Badruel Hairiel; Mohamad Diah, Nurazzura; Mohd Jani, Haizuran; Ahmad, Abdul Sham (IIUM Press, International Islamic University Malaysia, 2019)
Sport is viewed as a multidimensional phenomenon. Most countries, including Muslim nations, invest heavily in sports to ensure the participation of their citizens both for recreational and competitive purposes. Indeed, the involvement of Muslim countries in significant multi-sport events such as the Commonwealth, the Asian, and the Olympic Games are inevitable. Therefore, a proper projection should be given to Muslim athletes as their participation reflects the identity and culture of Muslim civilizations. To date, the issue of Muslim athlete’s involvement in sports from the notion of Islamization has yet to be elucidated by any scholar. This paper aims to scrutinize the sports sociology as an academic discipline in the Muslim majority society context. It also views the philosophy of sports participation and the dilemma faced by Muslims in sports under the light of al- Qur’ān, and Hadith. In obtaining relevant information for this paper, we employed qualitative content analysis from various literature. In conclusion, this discourse of sport, Islam, and society has potentially triggered the new social movement that accommodated the needs of the Muslim community towards sports participation and physical activity.